Status of organizational practices of paraclete foundation community school inc. - Dimapilis, Antonia L. (Manila : National University, 2015)
The importance of this research lies in its immediate usefulness in providing initial information on the organizational practices of Paraclete Foundation Community School Inc.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of contents -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Methodology -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendation -- Bibliography -- Appendices.
Research Method : Descriptive Method.
Includes bibliographical references.